Organizational and management features of activity Virtual scientific biographical laboratory - Vernik Yuliia (Bìblìotečnij vìsnik, 2024)

(untitled)
The purpose of the article is a comparative analysis of ways of organizing scientific and professional activities among traditional formal, informal groups and virtual associations of scientists. The research methodology is based on a combined methodological approach, including the analysis of literary sources, statistical data, and empirical observations. The materials used allow you to get a comprehensive view of the researched topic. The scientific novelty consists in a detailed examination of modern trends in virtual cooperation and the identification of their impact on the scientific process in the humanitarian dimension. The specifics of virtual scientific associations are studied, their possibilities for the implementation of scientific projects, as well as ensuring flexibility and cooperation in the scientific environment are revealed. Conclusions. The research findings emphasize that the organization of virtual scientific associations and the effective use of online tools are becoming a key component of modern scientific activity, particularly in the humanitarian dimension. The main emphasis is on how information and communication technologies affect the efficiency and effectiveness of such associations in conducting scientific research and joint activities. The study addresses the current topic of the growing integration of information and communication technologies in the scientific process, especially in the humanitarian sphere, and analyzes the impact of this integration on traditional methods of scientific work. A number of benefits of this approach have been identified, including increased availability of resources, improved communication and collaboration between scientists, and challenges that require further study. Based on the analysis, recommendations are presented for optimizing the work of virtual scientific groups in order to increase the efficiency of conducting research and joint scientific projects, including management strategies, the use of specialized scientific platforms and tools for flexible project management, and promoting the innovative potential of scientists in a virtual environment.